Between Trauma and Nostalgia: Second Generation Memory of the War in Bosnia and Herzegovina - Wasiak, Katarzyna (Historia i Polityka, 2023)
In this article, the author set out to analyze the war narratives of the Bosniak second generation – the generation that de facto did not experience the war, and base their stories on the experiences of their loved ones. The author shows how family narratives about the war affect the contemporary lives of those born after the war, and most importantly, how they affect contemporary ethnic relations in Bosnia.